No difference found in safety or efficacy of balloon atrial septostomy performed at the bedside versus the catheterisation laboratory. (28th August 2018) - Savorgnan, Fabio; Zaban, Nicholas B.; Elhoff, Justin J.; Ross, Michael M.; Breinholt, John P.
Abstract: Background: Balloon atrial septostomy is performed in infants with dextro-transposition of the great arteries to improve oxygenation before surgery. It is performed in the catheterisation laboratory with fluoroscopy or at the bedside using echocardiography. It is unclear whether procedural safety and efficacy is superior in one location versus the other, although the bedside procedure may improve resource utilisation and present an opportunity for reducing cost. This study compares safety and efficacy of atrial septostomy performed at the patient's bedside versus the catheterisation laboratory. Methods: Neonates with dextro-transposition of the great arteries who underwent balloon atrial septostomy from October, 2000 to January, 2014 were included. Medical and procedural records, echocardiograms, and catheterisation data were reviewed. Comparisons between the two procedural locations included patient demographics, pre- and post-procedure oxygen saturations, and outcomes. Complications reviewed included bleeding, arrhythmia, cardiac trauma, stroke, and death. Coronary artery evaluations were recorded. T-tests were used for continuous variables, and Fisher's exact tests were used for all categorical variables. Wilcoxon rank sum and analysis of covariance modelling were used for time variables and oxygen saturation, respectively. Results: A total of 88 infants met the inclusion criteria. Among them, 53 underwent septostomy at the bedside and 35 underwent septostomy in the catheterisation laboratory. No safety or outcome benefit was identified between the two procedural locations. Conclusion: Septostomy performed at the bedside and in the catheterisation laboratory had similar outcomes and efficacy. Further, bedside septostomy has the advantage of no radiation exposure, and obviating risks with patient transfer from the ICU to the catheterisation laboratory.